4a-3a(a-2)=2(3a-2)

Simple and best practice solution for 4a-3a(a-2)=2(3a-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4a-3a(a-2)=2(3a-2) equation:


Simplifying
4a + -3a(a + -2) = 2(3a + -2)

Reorder the terms:
4a + -3a(-2 + a) = 2(3a + -2)
4a + (-2 * -3a + a * -3a) = 2(3a + -2)
4a + (6a + -3a2) = 2(3a + -2)

Combine like terms: 4a + 6a = 10a
10a + -3a2 = 2(3a + -2)

Reorder the terms:
10a + -3a2 = 2(-2 + 3a)
10a + -3a2 = (-2 * 2 + 3a * 2)
10a + -3a2 = (-4 + 6a)

Solving
10a + -3a2 = -4 + 6a

Solving for variable 'a'.

Reorder the terms:
4 + 10a + -6a + -3a2 = -4 + 6a + 4 + -6a

Combine like terms: 10a + -6a = 4a
4 + 4a + -3a2 = -4 + 6a + 4 + -6a

Reorder the terms:
4 + 4a + -3a2 = -4 + 4 + 6a + -6a

Combine like terms: -4 + 4 = 0
4 + 4a + -3a2 = 0 + 6a + -6a
4 + 4a + -3a2 = 6a + -6a

Combine like terms: 6a + -6a = 0
4 + 4a + -3a2 = 0

Factor a trinomial.
(2 + -1a)(2 + 3a) = 0

Subproblem 1

Set the factor '(2 + -1a)' equal to zero and attempt to solve: Simplifying 2 + -1a = 0 Solving 2 + -1a = 0 Move all terms containing a to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1a = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1a = 0 + -2 -1a = 0 + -2 Combine like terms: 0 + -2 = -2 -1a = -2 Divide each side by '-1'. a = 2 Simplifying a = 2

Subproblem 2

Set the factor '(2 + 3a)' equal to zero and attempt to solve: Simplifying 2 + 3a = 0 Solving 2 + 3a = 0 Move all terms containing a to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 3a = 0 + -2 Combine like terms: 2 + -2 = 0 0 + 3a = 0 + -2 3a = 0 + -2 Combine like terms: 0 + -2 = -2 3a = -2 Divide each side by '3'. a = -0.6666666667 Simplifying a = -0.6666666667

Solution

a = {2, -0.6666666667}

See similar equations:

| 2[5x-2(5x+y)]= | | 7(n+9)-6(7n-3)= | | y=.4*-27 | | 4X-24=36 | | y=.4x*27 | | 1/x=2/x+2 | | 3x-12=1x | | 7x+5=37 | | 1/25-5=x | | 322yds=73yds | | X(x-3)=36 | | -0.7x=1.4 | | 4y-8=64 | | 2.35+p=49.25 | | (X/5)=(6/35x)+2 | | v/3+17=30 | | 12=u/2-13 | | 11(q-4)-2(7q+4)= | | u/5=6.25 | | 5/6x-1/6y=19/6 | | h(t)=-16t^2+26t+6 | | p=20n-(12n+200+2.5n) | | y=10x+30000 | | 6(n-6)=12 | | 6y=15.36 | | 7007cm^2=77cm | | 9.6=w/3 | | 8=v/20.48 | | 15m+75-24m+21= | | 2+.70x+4.00=27.00 | | z^2+18=10 | | 2=E+2 |

Equations solver categories